Measuring Device for More Precise Mistuning Identification of Integrated Bladed Discs - Kučera, Ondřej; Píštěk, Václav; Fomin, Oleksij; Kučera, Pavel; Sagin, Sergii (MDPI, 2025)
In integrated turbine wheel designs, small deviations, known as mistuning, often occur in the modal properties of individual blades due to manufacturing tolerances and material inhomogeneity. During operation, this mistuning can cause some rotor blades to be subjected to significantly higher loads than predicted for an ideal rotor. The degree of rotor mistuning can only be determined using methods of experimental modal analysis. However, the manual use of the modal hammer cannot ensure precise repeatability of the force impulse’s location and timing, leading to inaccuracies. This article introduces a mechanism that replaces manual modal hammer operations, guaranteeing consistent impact location and timing while eliminating double strikes. The device was verified on bladed discs of various sizes, and its usability is demonstrated in this article on a turbine wheel of a marine engine turbocharger. The developed mechanism automates modal hammer strikes, ensuring precisely repeatable force courses and positioning for each impact. This automation reduces the measurement time and significantly improves the accuracy. The results of this research showed that even with careful manual operation of the modal hammer by an experienced operator, statistically significant differences arise in the repeated measurements of a bladed disc mistuning, whereas with the use of the presented measuring device, the results of the repeated measurements are practically identical.

In integrated turbine wheel designs, small deviations, known as mistuning, often occur in the modal properties of individual blades due to manufacturing tolerances and material inhomogeneity. During operation, this mistuning can cause some rotor blades to be subjected to significantly higher loads than predicted for an ideal rotor. The degree of rotor mistuning can only be determined using methods of experimental modal analysis. However, the manual use of the modal hammer cannot ensure precise repeatability of the force impulse’s location and timing, leading to inaccuracies. This article introduces a mechanism that replaces manual modal hammer operations, guaranteeing consistent impact location and timing while eliminating double strikes. The device was verified on bladed discs of various sizes, and its usability is demonstrated in this article on a turbine wheel of a marine engine turbocharger. The developed mechanism automates modal hammer strikes, ensuring precisely repeatable force courses and positioning for each impact. This automation reduces the measurement time and significantly improves the accuracy. The results of this research showed that even with careful manual operation of the modal hammer by an experienced operator, statistically significant differences arise in the repeated measurements of a bladed disc mistuning, whereas with the use of the presented measuring device, the results of the repeated measurements are practically identical.
Measuring Device for More Precise Mistuning Identification of Integrated Bladed Discs
Keywords: bladed disc; mistuning; measuring device; turbocharger; marine engine; bladed disc; mistuning; measuring device; turbocharger; marine engine